Myocardial Ischemia Detection by a Sensitive PumpProbe Atomic Magnetometer: Cardiac Ischemia Detection by Atomic Magnetometers - Zamani, Amin; Ranjbaran , Maliheh; Tehranchi, Mohammad Mehdi; Hamidi, Seyedeh Mehri; Khalkhali, Seyed Mohammad Hosein (Journal of Lasers in Medical Sciences, 2022)
Introduction: Magnetocardiography (MCG) based on optical atomic magnetometers has shown promise for detecting heart diseases accurately. Different methods were introduced to improve the sensitivity of detecting magnetic fields during cardiac activity. Methods: In this paper, an optical pump-probe magnetometer operated on the ground-state Hanle effect based on the zero-field level crossing technique was developed and the laser output signal was optimized in an unshielded environment. Then, the optical magnetometer was utilized to record the simulated MCG trace of different stages of myocardial ischemia. Results: The probe output light intensity followed the variation of cardiac magnetic field (MCG trace) generated by the Helmholtz coil accurately. Conclusion: Based on the results, the feasibility of our highly sensitive optical magnetometer in tracing showed no change in the P-QRS-T waveform associated with ischemic heart disease (IHD), where P indicates atrial depolarization, QRS is responsible for ventricular depolarization, and T represents ventricular repolarization. Doi:10.34172/jlms.2022.24.